2018
DOI: 10.1002/crq.21216
|View full text |Cite
|
Sign up to set email alerts
|

Retaining volunteer mediators: Comparing predictors of burnout

Abstract: Retention of the estimated 30,000 U.S. volunteer community mediators is critical to provision of high‐quality services. Although workers’ retention and burnout is well researched, retention of volunteers such as community mediators is less understood. Survey data of 53 volunteer mediators were analyzed. For volunteer mediators, burnout and intent to remain for 2 years were significantly negatively associated. Using a self‐determination‐based basic needs satisfaction scale, more relatedness satisfaction predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Harmon-Darrow & Xu compared predictive variables of burnout, exploring strategies to retain volunteer mediators. They discovered that enhancing lateral associations among mediators could be an effective and pragmatic management strategy, serving well the participants, volunteer mediators, and programs, and preventing job burnout [33].…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Harmon-Darrow & Xu compared predictive variables of burnout, exploring strategies to retain volunteer mediators. They discovered that enhancing lateral associations among mediators could be an effective and pragmatic management strategy, serving well the participants, volunteer mediators, and programs, and preventing job burnout [33].…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Future research might examine the resilience factors or personal traits that mediate the effect of burnout and turnover intentions despite the perceived high stress or low scores on specific components of the Adaptive Reserve Scale. The mediating factors explored in other fields include emotional competence (Rey et al, 2016); cognitive appraisal in evaluating the ability to cope (Gomes et al, 2013); coping resources (cognitive restructuring and functional beliefs; Gnilka et al, 2017); and relatedness satisfaction (Harmon-Darrow & Xu, 2018). In the context of the COVID-19 pandemic, meaningful living positively correlates with resilience and psychological wellbeing (Arslan et al, 2020).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Yet, with this habituated change, the risk of burnout from the emotionally intensity of such experience was possible, most notably when the practitioner observed enhanced suffering despite their efforts toward conflict mitigation. A recent study has shown that a significant number of conflict resolution volunteers who were trained to offer mediation serve experienced burnout in the form of increased emotional exhaustion and a decreasing sense of personal accomplishment (Harmon‐Darrow & Xu, ).…”
Section: From Systemic Practices To Strategic Techniquesmentioning
confidence: 99%